PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN MIGAS DI BURSA EFEK INDONESIA PERIODE 2016–2020) - Muh. Akbar Muktadirun; Buyung Sarita; Sujono Sujono; Riski Amalia Madi (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
This study aims to determine the Effect of Fundamental Factors on Stock Prices (Study on Oil and Gas Mining Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2016–2020 Period). The population of this study is the oil and gas mining sub-sector companies, totaling 9 companies. The sample was determined using purposive sampling method, to get a sample of 7 companies. The analytical method used is panel data regression analysis and processed using the Eviews 9 application. Based on the results of the study, it shows that Earning Per Share (EPS), Price to Earning Ratio (PER) and Company Size have a positive and significant effect on stock prices. Meanwhile, Net Profit Margin (NPM) and Debt to Equity Ratio (DER) have a positive and insignificant effect on stock prices. On the other hand, Return On Equity (ROE) has a negative and insignificant effect.